Website Content Evaluation Instrument for Adoption of Digital Publishing Innovations - and Nkechi Christopher, Emmanuel Ifeduba (International Journal of Scientific Research and Management (IJSRM), 2016)
Digital publishing is currently a major area of growth in the publishing sector of the global economy andpublishers, in realization of this development, are increasingly going digital, and going digital entailsadopting at least some of the innovations necessary for profitable business. To understand which innovationsthat are adopted by pioneer e-publishers to assess them for possible adoption, scholars and publishers,especially those based in developing economies would need reliable website evaluation instruments, but mostinstruments available for website analysis are not focused on publishing. This gap, therefore, needs to befilled with instruments specifically targeted at publishing sites. This study reports the development procedurefor a web evaluation instrument targeting publishing-specific websites. The 34-item instrument measures fiveaspects of digital publishing: digital book format, e-promotion, e-commerce, e-collaboration and esocialization.A total of 79 websites were observed and the proposed instrument was used to collect data toexamine level or extent of implementation of digital publishing. The results indicate that the instrument isreliable. It is, therefore, concluded that the instrument will be useful to media scholars and publishers.